2019
DOI: 10.1029/2018gb006129
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Acetate as a Microbial Carbon and Energy Source in the Water Column of Gulf of Mexico: Implications for Marine Carbon Cycling

Abstract: Acetate is a key intermediate of organic matter mineralization, but its metabolism remains largely unconstrained in the pelagic ocean. We conducted an integrated biogeochemical study to investigate microbial acetate cycling in the northern Gulf of Mexico with the goal of elucidating the importance of acetate as a carbon and energy source. Acetate was used primarily as an energy source, as evidenced by observed oxidation rates (rate constant k: 0.06–0.22 day−1) that varied between 42% and 96% of total biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…The genomic and enzymatic evidence provided by this study of acetate production by ANME-2a could explain the existence of the large heterotrophic communities in cold seep ecosystems, as acetate is a popular carbon source for marine ecosystems. In surface water, acetate has been identified not only as an energy source but also as an important carbon source incorporated into biomass (accounting for 58% of total uptake) by heterotrophic bacteria 32 . In anoxic sediments, acetate was found to be utilized primarily by non-methanogenic heterotrophs as an energy and carbon source, and approximately 10-76% was assimilated into biomass for cell growth 10,33 .…”
Section: Discussionmentioning
confidence: 99%
“…The genomic and enzymatic evidence provided by this study of acetate production by ANME-2a could explain the existence of the large heterotrophic communities in cold seep ecosystems, as acetate is a popular carbon source for marine ecosystems. In surface water, acetate has been identified not only as an energy source but also as an important carbon source incorporated into biomass (accounting for 58% of total uptake) by heterotrophic bacteria 32 . In anoxic sediments, acetate was found to be utilized primarily by non-methanogenic heterotrophs as an energy and carbon source, and approximately 10-76% was assimilated into biomass for cell growth 10,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Although acetate is considered a fermentation product, rapid acetate uptake has been reported in several aquatic ecosystems, including surface oxic marine waters (Ho et al, 2002). Zhuang et al (2019) recently revealed the high relevance of acetate as a metabolic substrate in the water column of the Gulf of Mexico. Acetate is primarily used as an energy source (evidenced by its high oxidation rates) and shows significant levels of assimilation into biomass, illustrating the potential significance of acetate as a carbon source that supports microbial growth (Zhuang et al, 2019).…”
Section: Acetate the Main Carbon Source Usedmentioning
confidence: 99%
“…Permanently sulfidic marine basins exhibit not only elevated rates of dark carbon fixation but also high rates of both acetate production and acetate assimilation (0.05 to 0.5 M day Ϫ1 ) (51). Acetate assimilation has been suggested to provide an important source of carbon for microbial growth on the highly productive northern Gulf of Mexico shelf (52). A. peruensis could assimilate acetate by converting it to acetyl-CoA using the combination of the high-affinity acetate permease (K m ϭ 5.4 M) and the acetyl-CoA synthetase (53,54) (Fig.…”
Section: Discussionmentioning
confidence: 99%